SNP discovery of PRKAB1 gene and their associations with growth traits in goats. Issue 7 (12th December 2022) - Zhou, Shengliang; Shi, Xiuying; Song, Chengchuang; Wang, Yanhong; Lai, Min; Chen, Xi; Zhang, Chunlei; Chen, Hong; Fang, Xingtang
Abstract: AMPK plays an important role in regulating the metabolism of carbohydrate, lipid and protein in an organism, and is considered to be a key regulator of cellular energy homeostasis. In recent years, attention has been drawn to AMPK subunit polymorphisms and their association with economical traits of domestic animals and fowls. PRKAB1 encodes the β1 regulatory subunit of AMPK, and it has been reported that PRKAB1 may be applied in breeding programs of meat-type chicken. To date, the polymorphism of goat PRKAB1 gene and its associations remain unknown. In this paper, the polymorphism of PRKAB1 gene was detected in 316 goats of three breeds. A total of four novel single nucleotide polymorphisms (SNPs) of PRKAB1 gene were revealed by sequence analysis. Among them, three were in the coding region (285 C > A, 297 C > A, 309 C > T), and they were all synonymous. One was in the intron (229 A > G). The associations between polymorphic loci and the growth traits of Xuhuai and Haimen goats were analyzed, and significant associations were found in body length index and trunk index ( p < 0.05) for Xuhuai breed, while no significant associations in Haimen breed. Our results provide useful information for the improvement and breeding of Chinese native goats.